Experimental Investigation and Exergy Analysis of Dehumidification Performances for a Cascaded Phase Change Heat Storage Dehumidifier - Lixi Zhang; Yi Jia; Zhida Fan; Kangbo Wang (Applied Sciences, 2022)
In the humidification and dehumidification solar desalination system, the recovery of vapor condensation latent heat is the key problem. Using a cascaded phase change heat storage method to recover vapor condensation latent heat can improve the phase change heat storage rate and the water production performance of dehumidifier. The exergy analysis and experimental methods are used to study the cascaded phase change storage dehumidifier. The results show that the more stages of phase change materials in the cascaded phase change heat storage device, the greater the exergy efficiency will be. The heat transfer performance of phase change materials increases with the increase of hot and wet air temperature and flow at the inlet of the dehumidifier. The exergy efficiency and gain output ratio of three-stage phase change heat storage are higher than that of the single-stage. The three-stage one is recommended. If the heat recovered by the cascaded phase change heat storage device is supplied to the passive humidification dehumidification desalinator for secondary water output, the water output and gain output ratio will increase by 25% and the water production cost will be reduced by 20%. The results can provide a basis for the design and application of a cascaded phase change heat storage dehumidifier.